Partial depletion of sarcoplasmic reticulum calcium does not prevent calcium sparks in rat ventricular myocytes. - Song, L S (1997)
1. The exact nature of calcium sparks in the heart remains highly controversial. We sought to determine whether calcium sparks arise from a single or multiple calcium release channels/ ryanodine receptors in the sarcoplasmic reticulum (SR). If their genesis involves a calcium-coupled recruitment of multiple channels, calcium sparks might be abolished by a modest depletion of SR calcium (because of the decrease in unitary calcium flux and hence a decrease in the gain of local calcium-induced calcium release). If, on the other extreme, calcium sparks are produced despite severe SR depletion, the single-channel origin will be preferred. 2. Spontaneous calcium sparks were studied in rat ventricular myocytes using confocal microscopy and the fluorescent calcium probe fluo-3. A computer algorithm was developed to count and measure objectively calcium sparks in linescan images. 3. Thapsigargin (25-150 nM) depleted caffeine-releasable SR calcium by up to 64%, in a dose- and time-dependent manner, without altering the resting cytosolic calcium level. During SR depletion, calcium sparks were robustly observed, albeit at reduced frequency (> or = 30% of control) and amplitude (> or = 60% of control). 4. Due to the reduced detectability of small sparks against noise background, the observed data would overestimate reduction in spark frequency but underestimate amplitude reduction. After correction for this detection bias, we found that the spark frequency was independent of SR load, whereas the amplitude was proportional to load. 5. We conclude that, although spark amplitude depends on SR filling status, the frequency of spark generation is independent of SR calcium load, and therefore independent of the local calcium release rate. This implies that sparks are single-channel events, or collective events that are well above threshold for local regeneration. Additionally, our results suggest that intraluminal SR calcium, at normal or low loads, does not play a major role in the regulation of on-gating of the ryanodine receptor.